1998
DOI: 10.1111/0033-0124.00133
|View full text |Cite
|
Sign up to set email alerts
|

Hispanic Community Types and Assimilation in Mex-America

Abstract: Terrence W. Haverluk United States Air Force AcademyI argue that discrepancies among Hispanic assimilation models can be interpreted through three distinct types of Hispanic communities-continuous, discontinuous, and new. Continuous communities were founded by Hispanics and Hispanics have always been the majority population. As a result, Hispanics have not assimilated as predicted by traditional models. Discontinuous communities were originally settled by Hispanics, but eventually were filled by a minority pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 6 publications
(11 reference statements)
0
17
0
Order By: Relevance
“…New communities were settled by Anglos, but later received a large number of Hispanic immigrants. Previous research has shown that Hispanics in New communities assimilate at higher rates than Hispanics in other communities, but not all New communities assimilate at the same rate (Haverluk 1998). In some New communities in Texas, Hispanics are now the majority and they have not assimilated.…”
Section: Pork Industrymentioning
confidence: 91%
See 1 more Smart Citation
“…New communities were settled by Anglos, but later received a large number of Hispanic immigrants. Previous research has shown that Hispanics in New communities assimilate at higher rates than Hispanics in other communities, but not all New communities assimilate at the same rate (Haverluk 1998). In some New communities in Texas, Hispanics are now the majority and they have not assimilated.…”
Section: Pork Industrymentioning
confidence: 91%
“…North Carolina Hispanic communities are considered "New" communities (Haverluk 1998). New communities were settled by Anglos, but later received a large number of Hispanic immigrants.…”
Section: Pork Industrymentioning
confidence: 99%
“…It is easy to imagine that the effects of acculturation will be different depending on the level of government under examination. Haverluk (1998) suggests the context into which individuals migrate significantly affects their acculturation. He identifies a type of community, which he labels continuous , where Mexican Americans have always been the majority population.…”
Section: Local Versus National Trustmentioning
confidence: 99%
“…A variety of studies have established the fundamental parameters of space and timing in the geography of the ethnic Mexican population (for excellent examples, see Nostrand 1970; Meinig 1971; Haverluk 1998; Arreola 2000). This patterning began with the creation of the Republic of Texas in 1836 and the signing of the Treaty of Guadalupe‐Hidalgo in 1848, which left a small population of ethnic Mexicans in parts of the Southwestern United States.…”
Section: The Historical Geography Of the Mexican‐origin Populationmentioning
confidence: 99%